Interference and facilitation in phonological encoding: Two sides of the same coin? Evidence from bilingual aphasia. (November 2020) - Calabria, Marco; Grunden, Nicholas; Iaia, Federica; García-Sánchez, Carmen
Abstract: In the present study, we explored the underlying mechanisms of lexical retrieval in two languages when modulated by phonological context. To do so, we investigated the performance of bilingual patients with aphasia and healthy bilingual individuals on a blocked cyclic naming task as a measure of lexical activation and phonological encoding within their two languages. Highly proficient Catalan-Spanish bilinguals with aphasia (n = 13) and controls (n = 15) were recruited for this study, all with language profiles consistent with early and balanced usage of their two languages. Participants completed a phonological blocked cyclic naming task where reaction times, word duration, and accuracy in naming were measured in each of their languages. Three main results were obtained: (1) overall, patients were slower and less accurate than controls; (2) in patients with aphasia, phonologically related items were named with less accuracy than unrelated ones, suggesting an interference effect of phonological overlap within lexical retrieval; (3) performance in terms of naming latencies showed no effect of phonological context and this was similar across both languages for patients and controls; and (4) word durations were unaffected by phonological context and item repetition, suggesting that phonological encoding may not have a cascading effect onto speech-motor planning. Additionally, individual level analyses confirmed that most of the patients were less accurate in naming pictures within the homogenous compared to the heterogeneous condition (9/13 patients in their dominant language and 11/13 in their non-dominant language). These findings are discussed within the context of language production theories that have attempted to explain facilitation and interference in blocking naming and their implications for bilingualism. Highlights: We explored the facilitatory effect during naming in bilingual patients. Accuracy was negatively impacted by phonological blocking in both languages. Phonological encoding would operate as language-independent process. Phonological and semantic relatedness impacts naming performance similarly.